2021
DOI: 10.1111/1365-2664.13845
|View full text |Cite
|
Sign up to set email alerts
|

Waterfowl use of wetland habitats informs wetland restoration designs for multi‐species benefits

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…Casazza et al. ( 2021 ) demonstrated that ducks are attracted to beneficial pond‐like features in sub‐optimal wetland habitats, such as tidal and sub‐tidal wetlands, and our study suggests that even relatively small or isolated natural and artificial habitats in or near commercial livestock facilities can attract waterfowl. Furthermore, even in our small sample size, we tracked multiple individuals to the same areas and facilities and several displayed the high site fidelity typical of waterfowl (Baldassarre, 2014 ; Nicolai et al., 2005 ), visiting the same sites repeatedly over months or across years.…”
Section: Discussionsupporting
confidence: 60%
“…Casazza et al. ( 2021 ) demonstrated that ducks are attracted to beneficial pond‐like features in sub‐optimal wetland habitats, such as tidal and sub‐tidal wetlands, and our study suggests that even relatively small or isolated natural and artificial habitats in or near commercial livestock facilities can attract waterfowl. Furthermore, even in our small sample size, we tracked multiple individuals to the same areas and facilities and several displayed the high site fidelity typical of waterfowl (Baldassarre, 2014 ; Nicolai et al., 2005 ), visiting the same sites repeatedly over months or across years.…”
Section: Discussionsupporting
confidence: 60%
“…There is evidence showing that restoring secondary habitat has benefits for species occurrence and abundance (Lewis-Phillips et al 2019;Casazza et al 2021), but can fail without understanding where restoration should occur and how to maximise these efforts (Sutherland et al 2004;Arlettaz et al 2010;Segan et al 2011). It is critical to investigate the value of secondary habitat and its capacity to compensate for the impacts of new developments on biodiversity, and whether these could provide a means to compensate for ongoing primary forest loss (Bennett et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While differences in geomorphic setting and/or application differentiate EWN ® projects, many have similar characteristics or needs related to performance evaluation. For instance, beach and dune, wetlands, and riverine systems projects all have vegetation components with similar benefits and goals (e.g., sediment trapping, increased habitat, promoting resilience to stressors; Cahoon et al 2020, Casazza et al 2021. Therefore, similar remote sensing data (e.g., lidar, red-edge sensors) and metrics (e.g., plant and community density; structural, vegetation, and floristic quality indices) could be used to assess the performance (e.g., changes in biomass) and impacts (e.g., elevation changes over time) of those projects.…”
Section: Remote Sensingmentioning
confidence: 99%